Use of active distance education methodologies during the pandemic – Academic Radio Project (Research, Society and Development, 2023)
Objective: Contribute with new ideas that can add to the teaching and learning of distance and/or face-to-face education where it is possible to develop digital media presentations. Method: this is an experience report where it was described the use of a strategy in the elaboration of contents that composed a seminar of presentations, unconventional, with a differential, the creation of “podcasts in radio program format”. Results: Eight synchronous meetings were held using Teams®, which resulted in the presentation of 22 podcasts with themes associated with communicable diseases that affect adults. Conclusion: Using this resource, students were able to associate theory with practice by doing an exercise in planning, decision-making, leadership, teamwork, evaluation and control.